Does Stenting as a Bridge to Surgery in Left-Sided Colorectal Cancer Obstruction Really Worsen Oncological Outcomes?. Issue 8 (August 2016) - Kwak, Min Seob; Kim, Wan Soo; Lee, Jeong-Mi; Yang, Dong-Hoon; Yoon, Yong Sik; Yu, Chang Sik; Kim, Jin Cheon; Byeon, Jeong-Sik
Abstract : BACKGROUND: Although self-expandable metal stents are used as a bridge to surgery in patients with colorectal cancer obstruction, their long-term oncological outcomes are unclear. OBJECTIVE: The aim of this study was to investigate long-term oncological outcomes of self-expandable metal stents as a bridge to surgery (stent group) compared with direct surgery (direct operation group) in patients with left-sided colorectal cancer obstruction. DESIGN: This was a retrospective chart review. SETTINGS: This study was conducted at a single tertiary academic center. PATIENTS: Of 113 patients who underwent curative surgery for left-sided colorectal cancer obstruction at Asan Medical Center between 2005 and 2011, 42 underwent direct surgery and 71 underwent self-expandable metal stent insertion followed by elective surgery. After 1:1 propensity-score matching, 42 patients were enrolled in both groups, and their postsurgical outcomes were compared. MAIN OUTCOME MEASURES: The primary outcomes of this study were long-term oncological outcomes, including overall survival and recurrence-free survival of patients in both groups. RESULTS: Three- and 5-year overall survival rates were similar in the stent (87.0% and 71.0%) and direct operation (76.4% and 76.4%) groups ( p = 0.931). Three- and 5-year recurrence-free survival rates were also similar in the stent (91.9% and 66.4%) and direct operation (81.2% and 71.2%) groups ( p = 0.581), as were postsurgical complication rates (9.5% and 16.7%; p = 0.344). No patient in either group experienced a permanent stoma. LIMITATIONS: This study was limited by its small patient numbers and retrospective nature. CONCLUSIONS: The long-term oncological outcomes of self-expandable metal stents as a bridge to surgery may not be inferior to those of direct surgery for left-sided colorectal cancer obstruction.